Beneath the rubble, the Crystal Palace! The surprising persistence of a temporary mega event. Issue 1 (1st January 2018) - Gardner, Jonathan
ABSTRACT: This paper considers the archaeological traces of some of the largest temporary gatherings imaginable: modern cultural mega events such as World's Fairs, Expositions and Olympic Games. Focusing specifically on what is widely accepted as the 'first' such event, The Great Exhibition of 1851, its aftermath and the rebuilding of its host structure, the Crystal Palace, the author investigates how mega events' archaeological traces can provide alternative accounts of the history of temporary spectacles. The author also highlights how an event sometimes becomes conflated with its structure, showing how the Crystal Palace's materials persisted long after the original gathering was over. Even after event sites take on radically different uses or their structures are moved, altered or totally destroyed, their scant traces can still inspire a desire for resurrection.